Fatal intracranial hemorrhage in a newborn with factor VII deficiency - Üçsel, Raif; Savaşan, Süreyya; Çoban, Asuman; Metin, Fazilet; Can, Gülay (The Turkish Journal of Pediatrics, 1996)
Factor VII deficiency is a rare congenital coagulopathy. Prolonged prothrombin time with normal partial thromboplastin time indicates factor VII deficiency. For the definitive diagnosis, the specific factor VII level should be investigated. We report a seven-day-old, male, full-term newborn who was admitted with the diagnosis of sepsis. Hematological tests revealed prolonged prothrombin time and a factor VII level of five percent. After antibiotic therapy and fresh frozen plasma replacement his clinical status improved but the prothrombin time continued to be prolonged. On the 14th day, just before the end of antibiotic therapy, the infant died of sudden intracerebral hemorrhage. In this article, the clinical features and management of factor VII deficiency are discussed.